How Early Can We Predict the Need for VPI Surgery?. Issue 11 (21st November 2022) - Pitkänen, Veera V.; Alaluusua, Suvi A.; Geneid, Ahmed; Vuola, Pia M. B.; Leikola, Junnu; Saarikko, Anne M.
Abstract : Background: Velopharyngeal dimensions change as a child with cleft palate (CP) grows. The aim of this study was to assess if the decision for velopharyngeal insufficiency (VPI) surgery can be made by the age of 3 years among CP children with moderate-to-severe VPI. In addition, we sought to clarify if speech therapy before VPI surgery is beneficial for VPI speech characteristics. Methods: This retrospective study reviewed documentation of children with moderate-to-severe VPI at age 3 years who did not undergo VPI surgery until age 5 years. Based on the national cleft register, 959 patients with syndromic and nonsyndromic CP were treated by the craniofacial team at Helsinki University Hospital, Finland between 2000 and 2014. Eighty-six patients fulfilled the study inclusion criteria. The speech pathologist evaluated velopharyngeal function at age 3, 5, and 8 years. Results: Of the 86 children presenting with moderate-to-severe VPI at age 3 years, 94% still had moderate-to-severe VPI at age 5 years, even though speech therapy was offered to 77%. Of those whose velopharyngeal function improved by age 5 years, function regressed to incompetent over time. Overall, 93% underwent VPI surgery and 82% underwent VPI surgery between ages 5 and 8 years. Only 23% at age 8 years still had moderate-to-severe VPI. Speech therapy alone did not improve VPI speech characteristics. Conclusions: Moderate-to-severe VPI did not improve from 3 to 5 years or improved but subsequently relapsed. This suggests that the decision for VPI surgery can be made for children aged 3 years with moderate-to-severe VPI.